2023
DOI: 10.1186/s13756-023-01243-x
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis on the prevalence of resistance of Staphylococcus aureus to different antibiotics in Nigeria

Abstract: Background Rapid emergence of multidrug resistant Staphylococcus aureus has resulted to difficulty in treatment of infections caused by such strains. The aim of this meta-analysis study was to determine the pooled prevalence of resistance of S. aureus to different antibiotics in Nigeria. Methods Literature search for studies was done using Google scholar, PubMed, Science direct, and African Journal Online. The prevalence of S. aureus resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
1
0
0
Order By: Relevance
“…This aligns with previous studies that have reported high rates of resistance to these drug classes in S. aureus isolates due to the production of the enzyme penicillinase/β-lactamase, which inactivates beta-lactam antibiotics [49], [50], [51], [52], [53]. Additionally, other studies [54], have documented multidrug resistance to these antibiotic classes.…”
Section: Discussionsupporting
confidence: 90%
“…This aligns with previous studies that have reported high rates of resistance to these drug classes in S. aureus isolates due to the production of the enzyme penicillinase/β-lactamase, which inactivates beta-lactam antibiotics [49], [50], [51], [52], [53]. Additionally, other studies [54], have documented multidrug resistance to these antibiotic classes.…”
Section: Discussionsupporting
confidence: 90%
“…represented the second most frequent Gram-positive uropathogen, emphasizing the highest rates of resistance to penicillin and trimethoprim-sulfamethoxazole. Even more worrying results than the present ones were published this year in a large metaanalysis in Nigeria [62], which showed the highest resistances to penicillins (over 80%) and aminopenicillins and the trimethoprim-sulfamethoxazole combination (over 50% of strains). Similar results were found in another study published this spring in Iran by Maryam Rafiee et al [63], noting over 85% of Staphylococcus strains resistant to penicillin, and showing susceptibility rates relatively similar to the present study for linezolid (84%) and levofloxacin (94%).…”
Section: The Resistance Profile Of Gram-positive Uropathogensmentioning
confidence: 41%
“…MRSA infections are considered potentially fatal due to the bacterium's ease of spread and resistance to treatment. The emergence of multi-resistant strains has further made therapy options difficult [2].…”
Section: Introductionmentioning
confidence: 99%
“…According to a meta-analysis, S. aureus resistance to several antibiotics ranged from 13 to 82% in Nigeria. The results from a study revealed the resistance of S. aureus to routinely used antibiotics in Nigeria to be 82% [2]. Furthermore, the increase in drug resistance is of a great concern and requires urgent attention.…”
Section: Introductionmentioning
confidence: 99%